Reverse Engineering of Plastic Waste into Useful Fuel Products - Owusu, Prosper Achaw; Banadda, Noble; Zziwa, Ahamada; Seay, Jeffrey; Kiggundu, Nicholas (Journal of Analytical and Applied Pyrolysis, 2018)
This paper’s twofold aims are: to assess the potential of converting plastic waste into useful fuels in both continuous and batch pyrolysis reactors using an appropriate technology and to investigate the effect of silica-alumina catalyst on the yield and quality of pyrolytic liquid oil. The plastic waste used (HDPE, PP and PS) were obtained from Kiteezi landfill site, Kampala (Uganda). In a further step, the properties of the liquid fuel obtained from pyrolysis were also compared with commercial transportation fuel to ascertain its suitability on diesel engines.The fuel qualities were analysed using ASTM standard test methods At a degradation temperature of 450 °C, thermal pyrolysis in a batch reactor resulted in the highest yield of liquid fractions. The liquid yield of HDPE, PP and PS was found to be 80%, 82.6% and 80% by mass, respectively. In contrast, silica-alumina catalyst to feedstock ratio of 1:10 was the most effective in terms of gaseous fraction production. The gaseous fractions were: 60 wt% for the mixture, followed by HDPE (59.63 wt%), PS (59.07 wt%) and PP (49.33 wt%). A catalyst/polymer ratio of 1:10 greatly reduced the degradation temperature. The degradation temperature for HDPE, PP and PS was reduced by about 33%, 23% and 17%, respectively. The liquid oils from HDPE and PP had densities of 0.796 g/cm3 and 0.786 g/cm3; kinematic viscosities of 2.373 mm2/s and 2.115 mm2/s, dynamic viscosities of 1.889 mPas and 1.856 mPas; boiling point ranges of 119–364 °C and 148–355 °C; and cetane indices of 46 and 63, respectively. The characteristics of HDPE and PP pyrolytic sample oils are similar to conventional transportation fuel.
Keywords: Plastic waste; pyrolysis; appropriate technology; silica-alumina; liquid oil